'They deserve a treat': the nature and antecedents of parental licensing surrounding children's physical activity. Issue 8 (28th June 2021) - Law, Kwok Hong; Dimmock, James A; Thornton, Ashleigh L; Nicholas, Joanna C; Ho, Gordon; Gucciardi, Daniel F; Guelfi, Kym J; Jackson, Ben
Abstract: Objective: Little is known about parents' compensatory health beliefs (CHB) surrounding their children's engagement in physical activity (PA). Our aim was to provide evidence regarding the nature of, and factors underpinning, parents' PA-related compensatory beliefs for their children. Design: A qualitative descriptive approach and thematic content analysis were employed. Setting: Parents were recruited from community sport and PA programmes. Participants: Eighteen parents aged 32–52 years (mean age = 40·8 (sd 5·4) years; six males; twelve females). Results: Analyses indicated that parents compensate through 'passive' or 'active' means. Among parents who compensated, most described their provision of 'treat' foods/drinks and a minority described allowing extended sedentary time to their children. Parents' reasons underpinning these beliefs related to their child's general physical/health status and psychological characteristics, and their own motivation and mood state. Conclusions: These findings provide the first evidence of unhealthy dietary and sedentary behaviour CHB that parents may hold regarding their children's involvement in PA.